Realismo mágico y literatura rabínica. La presencia del Infierno y de la Muerte en el mundo de los vivos - Miralles Maciá, Lorena (’Ilu. Revista de Ciencias de las Religiones, 2004)
In this investigation we study several Talmudic texts, in which magic elements play an important role in the rabbinical reality. We can find the sensibility to explain these passages in the trend known as “realismo mágico” or “lo real maravilloso”. The works we have chosen are G. García Márquez’ Cien Años de Soledad and J. Rulfo’s Pedro Páramo, because not only they are two masterpieces of the Hispano-American narrative, but they have been also translated into most of Occidental languages. The fields of this article are the dead and the hell, with their representations in the living’s world. In the Latino-American novel and in the Rabbinical universe the demons, the mediators and all of kinds of intermediate beings are connected with people throught a mythic reality. So, in spite of being two literatures distant in time and space, they can have a similar sensibility to approach the questions of the afterlife, without leaving the reality and without loosing the spontaneity of the traditional and popular culture, which adores the magic elemen